2012
DOI: 10.7324/japs.2012.21113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cynoglossum zeylanicum (Vehl ex Hornem) Thunb. Ex Lehm on Oral Glucose Tolerance in rats

Abstract: The effect of ethanol extract of whole plant of Cynoglossum zeylanicum on Oral Glucose Tolerance was determined. Ethanol extract of Cynoglossum zeylanicum were evaluated for Oral Glucose Tolerance Test (OGTT) in normal and alloxan induced diabetic rats. Oral administration of ethanol extract at doses of 100 &150mg/kg body weight shows that the extract promote glucose uptake. These results suggest that the ethanol extract of Cynoglossum zeylanicum whole plant will be useful in the treatment of impaired oral glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…DOI: http://dx.doi.org/10. 22192/ijcrcps.2017.04.04.004 Hyperglycemia is an important factor in the development and progression of the complications of diabetes mellitus (Anitha et al, 2012). Several medicinal plants have been found to be successfully in diabetes treatment and some of them have been tested and their active ingredients isolated (Grover et al, 2002;Shu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…DOI: http://dx.doi.org/10. 22192/ijcrcps.2017.04.04.004 Hyperglycemia is an important factor in the development and progression of the complications of diabetes mellitus (Anitha et al, 2012). Several medicinal plants have been found to be successfully in diabetes treatment and some of them have been tested and their active ingredients isolated (Grover et al, 2002;Shu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Two case studies of oral glucose tolerance in rats [2,14] are showed to analyze. In the present investigation, 36 normal rats were fasted for 12h and assigned randomly into 6 equal groups (n= 6/group) [14].…”
Section: Results and Practical Data Of Oral Glucose Tolerance Testmentioning
confidence: 99%
“…In the other investigation, a total 20 normal rats were taken and divided into four groups for oral glucose tolerance test (each group 5 rats) with an antihyperglicemic plant, Cynoglossum zeylanicum (Boraginaceae) [2]. The concentrated ethanol extract of this medicinal plant was used for the oral glucose tolerance test.…”
Section: Results and Practical Data Of Oral Glucose Tolerance Testmentioning
confidence: 99%
“…Apart from using fasting blood glucose alone, OGTT was seen as a practical attempt to simplify and facilitate the diagnosis of diabetes [20]. An oral glucose tolerance test helps in checking on the ability of an organism to regulate blood glucose 2 hrs after receiving 2 g/Kg b.w.…”
Section: Discussionmentioning
confidence: 99%